Hubungan kontrol diri dengan prestasi belajar siswa - Citra Putri Intani; Ifdil Ifdil (Indonesian Institute for Counseling, Education and Therapy (IICET), 2018)
Student achievement is found apda initial survey is still much under KKM while individuals who have high self-control can direct and manage his behavior, not easily tempted by changes that occur and can avoid the deviant behavior, This study aims to analyze the relationship control self with student achievement with the strength of the relationship is quite strong in students at SMA Negeri 7 Padang. This type of research is quantitative research with the type of research is descriptive correlational research. The population of this study class XI and class XII SMA Negeri 7 Padang 2017/2018 as many as 596 students and a sample of 240 students. Sampling using simple random sampling technique. Instrument used for research in the form of closed questionnaire to know the relationship of self control with student achievement by using correlation test. The results revealed: 1) students' overall self-control was in the moderate category with the percentage of 38.8% 2) the overall student learning achievement (26.7%) with the learning achievement score 62-67, and there was a significant relationship between self-control with learning achievement at SMA Negeri 7 Padang.